Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
Answer is the first one, i know tricks boy
Step-by-step explanation:
The given function f(x) is equivalent to (x-8((x-3).
We have given function is,
[tex]f(x)=x^2-5x-24[/tex]
We have to find the equivalent expression of the f(x).
What is the ac method?
The ac Method is a method of factoring trinomial in the form
[tex]ax^{2} + bx + c=0[/tex].....(1)
The ac method of factoring is basically a method to that you can eventually factor the trinomial using grouping. In order to split the middle term (in this case bx), we will need to find the factors that make up the product of the coefficient a and c.
Compare the the given function with equation 1 and find the value of a,b,c
[tex]f(x)=x^2-5x-24[/tex]
by given polynomial
a=1,b=-5 and C=-24
By using AC method
ac=(1)(-24)
ac=-24=-8(3)
b=-8+3=-5
[tex]=x^2-8x-3x-24\\\\=x(x-8)+3(x-8)\\\\=(x-8)(x+3)[/tex]
Therefore,
The given function f(x) is equivalent to (x-8((x-3).
To learn more about the equivalent expression visit:
https://brainly.com/question/24734894
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.